PELAKSANAAN ADAT PERKAWINAN DAYAK NGAJU Dalam Pusaran Perubahan Sosial dan Eksistensi Gereja Kalimantan Evangelis - Telhalia . (Studia Philosophica et Theologica, 2016)
The Dayaks move in the framework of custom traditions, and provisions inherited by their ancestors. Therefore, customs have a significant relevance with the structure of religious of the Dayaks. The encounter between Christianity and Dayak culture from the beginning has generated much controversy. The main issues encountered in various regions as that it is difficult to separate between religion and culture. The birth of the churches in Indonesia in the form of tribal church was influenced by certain thoughts (volkskirche) in their theology of evangelization in Western Europe in the century of XIX. For instance, the establishment of the Evangelical Church of Kalimantan; as a church, it still lacks the distinctive signs of Dayak culture. While the Evangelical Church of Kalimantan grows and lives in the midst of nature. Humans are obliged to maintain the equilibrium of nature that is part of human life. To maintain the equilibrium of nature, humans exbibit behaviors that maintain relationship with nature, other creatures and the ruler of the universe. Contextual theology is an effort to explain problem facing society in the light of faith.